Local Open Government: Key Issues in Paris - Afandi, Syed Agung; Afandi, Muslim; Erdayani, Rizki (Malikussaleh Social and Political Reviews, 2024)
This study aims to analyze key issues of open government in Paris. The city is one of the selected members of the Open Government Partnership (OGP) for the Local Government Pilot Program. A qualitative approach and bibliometric analysis method are used in this study. Data sourced from Google Scholar collected using Publish or Perish (keywords: Paris information access; Paris transparency; Paris public participation; and Paris public collaboration). Data selection using Mendelay, while bibliometric maps obtained using VOSviewer. This study found 90 relevant articles and 90 topics of open government in Paris. The dominant topics include: transparency; Paris agreement; information; guidelines; and access. While the current and potential topics include: communications; challenges; capacity; policy-making; and hidden-order procedure. Since its main role in the Open Government Partnership, Paris has set twelve commitments, four of which are their current focus: Paris citizens assembly; introducing two brand-new digital platforms for greater transparency and citizen participation; European citizenship; developing the first index to assess ecological democracy, and establish an action to implement the UNFCCC Action for Climate Empowerment program. These commitments are part of the current potential study of open government in Paris.